Temperature and Sex Ratios at Birth - Jasmin Abdel Ghany; Joshua Wilde; Anna Dimitrova; Ridhi Kashyap; Raya Muttarak (Institute of Labor Economics (IZA), 2024)
Sex ratios at birth shape populations and are linked to maternal health and gender discrimination. We estimate the effect of prenatal temperature exposure on birth sex by linking data on 5 million births in 33 sub-Saharan African countries and India with high-resolution temperature data. We find that days with a maximum temperature above 20°C reduce male births in both regions. In sub-Saharan Africa, we observe fewer male births after high first trimester temperature exposure, consistent with increased spontaneous abortions from maternal heat stress. By contrast, in India we find second trimester temperature exposure is associated with fewer male births, consistent with reductions in induced sex-selective abortions against girls. These findings demonstrate that climate change harms maternal health, increases prenatal mortality, and reduces engagement with the health system.
Keywords: J13; J10; I15; I10; O13; 330; sex ratios at birth; temperature; prenatal exposure; maternal health; abortion